The evolution of infant mortality and neighbourhood inequalities in four world cities: 1988–2016. (26th January 2022) - Weisz, Daniel; Gusmano, Michael K.; Laborde, Caroline; Feron, Valerie; Rodwin, Victor G.
Abstract: Objectives: To determine the level of neighbourhood inequalities in infant mortality (IM) rates in the urban core of four world cities and to examine the association between neighbourhood‐level income and IM. We compare our findings with those published in 2004 to better understand how these city health systems have evolved. Methods: We compare IM rates among and within the four cities using data from four periods: 1988–1992; 1993–1997; 2003–2008 and 2012–2016. Using a maximum‐likelihood negative binomial regression model that controls for births, we predict the relationship between neighbourhood‐level income and IM. Results: IM rates have declined in all four cities. Neighbourhood‐level income is statistically significant for New York and, for the two most recent periods, in Paris. In contrast, there is no significant relationship between neighbourhood income and IM in London or Tokyo. Conclusions: Despite programmes to reduce IM inequalities at national and local levels, these persist in New York. Until the early part of this century, none of the other cities experienced a relationship between neighbourhood income and IM, but growing income inequalities within Paris have changed this situation. Policy implications: Policy‐makers in these cities should focus on better understanding the social and economic factors associated with neighbourhood inequalities in IM. Highlights: Manhattan has a strong negative relationship linking neighbourhood income and infant mortality (IM). Paris, since 2003, has a negative relationship between neighbourhood income and IM. Inequalities in IM rates in cities are influenced by national health and social policies. Reducing neighbourhood inequalities requires targeted public health approaches.